Analisis Perilaku Pelanggan Terhadap Produk Somethinc - Putri Wijayanti Kusuma; Nita Apriyanti; Syamsul Hidayat (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The phenomenon of Indonesians' increasing need for skincare products is the purpose behind this research. Similarly, Somethinc skincare products emerged and showed optimal performance, causing the product to go viral. The purpose of this study is to determine how customer behavior towards Somenthinc products. This research method is quantitative and the data analysis method used is descriptive statistical analysis. The sample was collected using a questionnaire in the form of a Likert Scale. The research methods carried out are validity and reliability tests, classical assumption tests, and descriptive statistical tests. The results showed that the relationship between customer behavior and Somethinc products had a positive influence or in other words, customers were able to refer Somethinc products to others.